Study of Rotation Effect on Nanofluid Natural Convection and Heat Transfer by the Immersed Boundary-Lattice Boltzmann Method - Tianwang Lai; Jimin Xu; Xiangyang Liu; Maogang He (Energies, 2022)
Aiming to investigate the rotation effect on the natural convection and heat transfer of nanofluid, which has an important application in the control of heat transfer, the velocity field and temperature distribution inside the square cylinder with the rotating heat source in the center were numerically studied and presented in detail at different Hartman numbers and aspect ratios using the immersed boundary-lattice Boltzmann method. Then, the average Nusselt number on the surface of the heat source was calculated to compare the heat transfer rate in different cases. The results showed that the rotation would reduce the effect of gravity on the flow and suppress the heat transfer between the rotating heat source and nanofluid, while the external magnetic field would reduce the rotation effect on the flow and suppress or promote the heat transfer depending on the rotational speed and aspect ratio. Moreover, the smaller aspect ratio of the heat source to the square cylinder would enhance the heat transfer rate and make the retarding effect of magnetic field on rotation more apparent. In addition, the dimensionless rotational speed was proposed in this work, by which much computational time could be saved during the calculation of the immersed-boundary lattice Boltzmann method for the problem of rotation.